Comparative Analysis of Nutritional Components and Phytochemical Attributes of Selected Thai Rice Bran - Wisetkomolmat, Jiratchaya; Arjin, Chaiwat; Satsook, Apinya; Seel-audom, Mintra; Ruksiriwanich, Warintorn; Prom-u-Thai, Chanakan; Sringarm, Korawan (Frontiers in Nutrition, 2022)
It is important to raise awareness regarding rice's nutritional quality and health benefits in terms of enhancing rice consumption in people's daily diets. This study evaluated the proximate components and phytochemical profiles of eleven Thai rice bran varieties, including four non-colored rice brans and seven-colored rice brans collected from the same agricultural fields. The chemical compositions (ash, fat, proteins, fiber, and gross energy) were determined using proximate analysis methods. High-performance liquid chromatography was used to analyze the γ-oryzanol, tocopherols, and anthocyanins, while gas chromatography-mass spectrometry determined the free fatty compounds. The phenolics profile was conducted using liquid chromatography-mass spectrometry. The results showed great variations in each parameter of nutritional and bioactive components among different rice bran varieties. Statistical analysis was also performed correlating the results obtained from PCA analyses to categorize the sample by their nutritional characteristics into three main groups; group A with a high content of protein and fiber, group B with a high content of fat and gross energy and group C with a low fat value and low energy but high amounts of functional active components, particularly γ-oryzanol. The anthocyanin were detected in only sample of colored rice bran. The major free fatty acid found in rice bran samples were oleic, linoleic, and palmitic acids. The systematic assessment of the concentration of these compounds gained from this study would be helpful to the industrial sector to select the phytochemical-rich varieties as a value-added component in nutritional products.